Development and evaluation of the BSC-DREAM8b dust regional model over Northern Africa, the Mediterranean and the Middle East - Sara Basart; Carlos Pérez; Slodoban Nickovic; Emilio Cuevas; José María Baldasano (Tellus: Series B, Chemical and Physical Meteorology, 2012)
The BSC-DREAM8b model and its predecessor are analysed in terms of aerosol optical depth (AOD) for 2004 over Northern Africa, the Mediterranean and the Middle East. We discuss the model performance and we test and analyse its behaviour with new components. The results are evaluated using hourly data from 44 AERONET stations and seasonally averaged satellite observations. The operational versions strongly underestimate the winter AOD over the Sahel and overestimate the AOD over the Middle East and the Mediterranean achieving a low average annual correlation (~0.35). The use of a more detailed size distribution and a corrected wash-out ratio, together with a new dry deposition scheme, improves the transport over the Mediterranean, although underestimations remain over the Sahel and overestimations over the Middle East. The inclusion of a ‘preferential source’ mask improves the localisation of the main North African sources and consequently the dust transport towards Europe and the Atlantic. The use of a more physically based dust emission scheme and a new soil texture database leads to significant improvements in the representation of emissions and the transport over the Sahel, achieving an average annual correlation of 0.53. In this case, the use of a preferential source mask does not introduce significant improvements.